Independent Curriculum and the Indonesian Language Education throughout the Era of Society 5.0: A Literature Review - Siti Rohana Hariana Intiana; Arina Amalia Prihartini; Fitriana Handayani; Mar'i Mar'i; Khairul Faridi (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to document the studies that have discussed the implementation of Independent Curriculum (Kurikulum Merdeka) in the Indonesian language subject. Indonesian language education focuses on the habituation of the use of Indonesian language in everyday communication life. Moreover, the world of education is currently faced with the era of Society 5.0 which is the integration of the virtual and the physical world by utilizing developments in technological advances to solve social problems. In line with these changes, teaching Indonesian language in the Independent Curriculum is also carried out through various project-based activities to encourage students to be skilful in producing works to understand concepts as well as apply them to solve actual problems (problem solving). This study employed a literature review as the design of the research. Five articles were collected as the corpus of the study. To analyze the data, a content analysis was utilized. The findings reported that Indonesian language education in the Society 5.0 era needs to be provided so that the students will have literacy skills in analyzing, understanding, and identifying solutions to problems encountered in everyday life. As a result, a person with a high level of literacy is able to acquire knowledge and information and apply digital technologies to improve their life's wellbeing.